Testing The Construction Of Physical Concepts Among Kindergarten Children (Journal of the College of Basic Education, 2024)
The current research aims to identify the structure of the physical concepts test for kindergarten children. The Listening Foundation tested the physical concepts after reviewing the theories and studies related to the subject of its research, as the physical concepts test includes (32) items distributed over nine sections, each area (4) items for each. In the field, the test instructions for each calculation were prepared and the scientific instructions for building the group were prepared. The test score was determined (0 - 1) with two alternatives to it (true - true). The automatic gain of the research tool was verified, represented by: honesty and consistency, and the validity of the two aspects was verified: honesty. Virtual, construct validity, and physical concepts were extracted using the test-retest method and the internal consistency coefficient of K 20 equation